The Influence of Cooperative Script Learning Method and Reading Habits on Student’s English Reading Comprehension - Fina Tri Yuniarti; Indawan Syahri; Masagus Firdaus (Journal on Education, 2024)
The purpose of this research was to analyze whether or there is a significant influence of the Cooperative Script Learning Method and reading habits on students' English reading comprehension. This research was conducted using experimental research methods. The research subjects were students of Eighth Grade Students at SMP Negeri 27 Palembang, with their parallel classes and there were 68 students. Each class consists of 34 students and the entire population is taken as a sample, then divided into two groups. high and low reading habit taught by Cooperative Script Learning Method. The instrument used to collect the data was a multiple choice test set. Pre-test and post-test were given. Data were collected statistically by applying the t-test formula. The results showed that the observed t was higher than the table value 9.710 > 1.690 at a significant level of 0.05 and the degree of freedom (df) was 33. The null hypothesis isrejected and the alternative accepted. This has a significant effect on the average reading comprehension between students with high and low reading habits when taught using the Cooperative Script Learning Method.